2021
DOI: 10.1021/acs.langmuir.1c01386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triton X-100 on the Activity and Selectivity of Lipase Immobilized on Chemically Reduced Graphene Oxides

Abstract: The effect of support hydrophobicity on lipase activity and substrate selectivity was investigated with and without Triton X-100 (TX-100). Lipases from Thermomyces lanuginosa (TL) and Alcaligenes sp. (QLM) were immobilized on graphene oxide (GO) and a range of chemically reduced graphene oxides (CRGOs) with different levels of surface hydrophobicity. Activity assays using 4hydroxy-N-propyl-1,8-naphthalimide (NAP) esters of varying chain lengths (NAPbutyrate (NAP-B), NAP-octanoate (NAP-O), and NAP-palmitate (NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The literature reported that the free TL has a high α-helicity. , Circular dichroism showed an increase in the hydrophobicity of the carrier and a consequent decrease in the α-helix of lipase TL, with only a 20% reduction after fixation on the GO carrier . This indicates that the mild amphiphilic surface is relatively friendly to the structural effects of TL.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The literature reported that the free TL has a high α-helicity. , Circular dichroism showed an increase in the hydrophobicity of the carrier and a consequent decrease in the α-helix of lipase TL, with only a 20% reduction after fixation on the GO carrier . This indicates that the mild amphiphilic surface is relatively friendly to the structural effects of TL.…”
Section: Introductionmentioning
confidence: 90%
“…34,35 Circular dichroism showed an increase in the hydrophobicity of the carrier and a consequent decrease in the α-helix of lipase TL, with only a 20% reduction after fixation on the GO carrier. 36 This indicates that the mild amphiphilic surface is relatively friendly to the structural effects of TL. Studies have shown that low-intensity ultrasound's alteration of the secondary structure of lipase TL increases its catalytic activity; 37 therefore, appropriate conformational changes are beneficial for lipase activity.…”
Section: Introductionmentioning
confidence: 96%
“…Then, a weak hydrophobic interaction disruptor, 1,6-hexanediol (Hdo), was employed, 49 and it was found that the T t was increased from 27 to 32 °C after the addition of Hdo, indicating that the hydrophobic interactions were disturbed (Figure 3d). Finally, we used a nonionic surfactant, Triton X-100 (TX-100), 50 to destroy the strong hydrophobic interaction. The sELP−ONs failed to form droplets after 1% TX-100 was added (Figure 3d).…”
Section: Insulin Encapsulation Efficiency (Ee)mentioning
confidence: 99%
“…22 In recent years, our focus has been on the preparation of 4-hydroxy-1,8-naphthalimides 23 and their use as biochemical reagents for determining lipase and esterase activity. 24,25 Recently, we developed a synthetic methodology to access 3,4-dialkoxy 1,8-naphthalimides, 17 which led to the preparation of the lipid droplet imaging probes DMN-LD and DMN-DT (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%